A construção da novidade: diálogos (im)pertinentes entre as teorias de Jean Piaget e Paulo Freire - Martins, Maria Elvira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The present thesis has the aim of building a dialogue between some aspects of two fundamental academic currents academic to Psychology and Education: Jean Piaget’s and Paulo Freire’s theories. With this intention, it shows, in a dialogical way, Jean Piaget’s functional aspects and notions of dialectic, interaction, activity, assimilation/ accommodation/adaptation, balancing (equilibração) and reflect adaptation/consciousness thinking and Paulo Freire’s functional aspects and notions of dialectic, interaction, activity, Liberating Education and transitive consciousness, looking for their similarities through dialogue. Understanding this dialogue as possible, the thesis looks forward discussing the importance of this theoretical meeting and aims at Transdisciplinarity Theory the path through this two theories and all who are involved inside the educational process/crossing/way can be potentialized in this educational and psychological meetings. Based on these theories, the thesis suggests a dialogical and, why not to say, happy and transcendent Education and Psychology for subjects and sciences inside this process

A presente tese tem o objetivo de construir um diálogo entre alguns aspectos funcionais de duas correntes fundamentais para as áreas da Psicologia e da Educação: as teorias de Jean Piaget e Paulo Freire. Com esta intenção, de forma dialógica, apresenta os aspectos e as noções funcionais de dialética, interação, atividade, assimilação/acomodação/adaptação, equilibração e adaptação reflexionante/tomada de consciência de Jean Piaget e os aspectos e as noções funcionais de dialética, interação, atividade, Educação Libertadora e consciência transitiva de Paulo Freire, buscando suas semelhanças em diálogo. Entendendo essa interlocução como possível, a tese pretende discutir a importância deste encontro teórico e busca, na Teoria Transdisciplinar o caminho para que as duas correntes teóricas e todos os envolvidos no processo/travessia/caminho educacional, sejam potencializados nestes encontros educacionais e psicológicos. Ancorada nestas teorias, propõe uma Educação e uma Psicologia dialógica e, por que não dizer, alegre e transcendente para os sujeitos e para as ciências envolvidos nesse processo
Keywords: Piaget, Jean, 1896-1980; Freire, Paulo, 1921-1997; Psicologia; Educação; Education